2020
DOI: 10.3390/nano10050825
|View full text |Cite
|
Sign up to set email alerts
|

Portable Instrument for Hemoglobin Determination Using Room-Temperature Phosphorescent Carbon Dots

Abstract: A portable reconfigurable platform for hemoglobin determination based on inner filter quenching of room-temperature phosphorescent carbon dots (CDs) in the presence of H2O2 is described. The electronic setup consists of a light-emitting diode (LED) as the carbon dot optical exciter and a photodiode as a light-to-current converter integrated in the same instrument. The reconfigurable feature provides adaptability to use the platform as an analytical probe for CDs coming from different batches with some variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Realizing the final application is the value of a material. 110,126,127,[144][145][146][147][148][149][150] information encryption, 113,115,118,119,121,123,128,[151][152][153][154][155][156][157][158][159][160] sensor detection, 114,124,129,130,147,[161][162][163][164][165][166][167][168][169][170][171][172][173][174] LEDs, [175][176][177][178]…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Realizing the final application is the value of a material. 110,126,127,[144][145][146][147][148][149][150] information encryption, 113,115,118,119,121,123,128,[151][152][153][154][155][156][157][158][159][160] sensor detection, 114,124,129,130,147,[161][162][163][164][165][166][167][168][169][170][171][172][173][174] LEDs, [175][176][177][178]…”
Section: Applicationsmentioning
confidence: 99%
“…It allows significantly increased time to visualize cell states, enables speedy detection, and also facilitates bioimaging and detection. Generally speaking, the RTP material based on CDs possesses huge application prospects in the field of anti-counterfeiting, 110,126,127,144–150 information encryption, 113,115,118,119,121,123,128,151–160 sensor detection, 114,124,129,130,147,161–174 LEDs, 175–179 biological imaging, 134,180,181 logic gates, 133 fluorescent ink 112,182–184 and other fields 116,117,122,185–195 with the properties of DF, TADF, long afterglow life and adjustable afterglow color.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct electrochemistry of proteins immobilized on an electrode surface has been studied as a way to sensitively detect H 2 O 2 without the need for an additional electron transfer mediator. Earlier studies have reported the immobilization of Hb on various electrode surfaces, such as glassy carbon electrodes [ 24 ], metal oxides [ 25 ], nanoparticles [ 26 ], carbon dots [ 27 ], and graphene [ 28 ], for achieving direct electron transfer toward sensing applications. However, there is a constant quest to achieve more efficient biosensors, i.e., characterized by better sensitivity and shorter response times, by employing minimal fabrication steps.…”
Section: Introductionmentioning
confidence: 99%